Caveolin-1 in Tumour Cells is Predominately Expressed in the Basal Subtype of Triple-Negative Breast Carcinoma - Savelina Popovska; Ivan Ivanov; Akishi Ooi (Journal of Biomedical & Clinical Research)
Triple-negative breast cancer (TNBC) is a subtype of breast cancer which is clinically negative for expression of steroid hormones and HER2 protein. According to DNA microarray profiling, breast cancer was divided into several molecular subgroups, including Luminal A and Luminal B; HER2 overexpressing; normal breast- like and basal-like subtype. TNBC comprises tumours that express heterogeneous molecular and immunohistochemical phenotype, thus determining different prognosis. The majority of TNBC carry the “basal-like” molecular profile on gene expression arrays. Basal-like carcinomas of the breast associated with poor prognosis often correlate with expression of Caveolin-1. The study aimed to investigate the expression of caveolin-1 in the tumour cells and in the stromal component of the tumour among the group of TNBC and compare it to the expression of caveolin-1 in a control group with non-TN breast cancer. Whole tissue sections were used. Formalin fixed, paraffin embedded tissue materials from 101 patients diagnosed with invasive breast cancer during the period 2004-2007 were investigated in a retrospective study. A multistep approach was used to separate the different subtypes of breast cancer. During the first step the breast tumours were separated according to their ER, PgR, HER 2 and proliferative activity, using the Ki-67 index. The triple- negative tumours were additionally tested for EGFR and CK5/6. The basal breast cancer group was finally subdivided into basal and baso-luminal according to the type of expression of basal cytokeratins. caveolin-1 expression was examined in the tumour parenchyma and stroma. According to our results, caveolin-1 expression in breast cancer was significantly associated with basal biomarkers expression (basal and baso-luminal type of BC) χ2= 33.4; p